(untitled) (Journal of Engineering, 2024)
The public procurement crisis in Iraq plays a fundamental role in the delay in the implementation of construction projects at different stages of project bidding (pre, during, and after). The procurement system of any country plays an important role in economic growth and revival. The paper aims to use the fuzzy logic inference model to predict the impact of the public procurement crisis (relative importance index and Likert scale) was carried out at the beginning to determine the most important parameters that affect construction projects, the fuzzy analytical hierarchy process (FAHP) to set up, and finally, the fuzzy decision maker’s (FDM) verification of the parameter for comparison with reality. Sixty-five construction projects in Iraq have been selected, and the most crucial crisis variables were used for calculating the weights and their importance, using the fuzzy logic inference model to verify the crisis parameters and the extent of their impact in preparation for predicting the mathematical model of public procurement parameters. After the algorithm had been completed, it was noted that the fast, messy genetic algorithm produced a little difference between training and testing (0.012% and 0.0057%), which is more reliable for predicting mean results from models. The paper’s major conclusion is that 18 crisis factors in public procurement through different stages affect construction projects in Iraq.